Empowering teen girls, Why are relationships so complicated? - Zager K.; Awareness Publishing Group (Pty) Ltd; Rubenstein A. (Gallo Manor: Awareness Publishing Group (Pty) Ltd, 2009)
A book about relationships, and how these change and develop during the teenage years. It explores the differences between girls and boys and how society treats males and females differently. It looks at good and bad relationships and how to deal with broken relationships.
Junior Non-Fiction-: Juvenile